The diet of the Antarctic fur seal Arctocephalus gazella at Harmony Point, South Shetland Islands: evidence of oportunistic foraging on penguins? - Casaux, Ricardo Jorge; Bellizia, L.; Baroni, A. (Polar Biology)
The analysis of 523 scats collected at Harmony Point, Nelson Island, South Shetland Islands, from January to March in 2001 and 2002, indicated that the diet of non-breeding male Antarctic fur seals Arctocephalus gazella was diverse and composed of both pelagic and benthic-demersal prey. Overall, the Antarctic krill Euphausia superba and fish were the most frequent and numerous prey, followed by penguins, cephalopods (mainly squid) and gastropods. Myctophids represented 86.5% and 65.8% of the fish mass in 2001 and 2002 respectively, with Gymnoscopelus nicholsi being the main prey. Interestingly, penguin remains were present in 39.0% and 31.9% of the samples in 2001 and 2002, respectively and these birds were the main prey by reconstituted mass (74.0% and 76.1% in both seasons). The occurrence of penguins in the diet of A. gazella at Harmony Point is discussed in terms of the foraging strategy employed by seals and the temporal availability of prey. Fil: Casaux, Ricardo Jorge. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Bellizia, L. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Baroni, A. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina